Disordered Skeletal Muscle Oxidative Metabolism In Human Obesity and Type 2 Diabetes - Antoun, Ghadi (Université d'Ottawa / University of Ottawa, 2016)
Obesity and type 2 diabetes mellitus (T2DM) are both complex diseases with multifactorial etiologies. Together they affect over 640 million people worldwide and have a significant impact on the global healthcare system incurring costs of over 800 billion dollars. The overall goal of my doctoral research has been to elucidate metabolic predictors and underlying mechanisms in obesity and T2DM. Specifically, I have examined mechanisms contributing to disordered oxidative metabolism in skeletal muscle. My research included participants who were recruited from the Ottawa Hospital Weight Management Clinic in which they completed a clinically supervised meal-replacement and lifestyle intervention program. More so, my doctoral studies evaluated characteristics of muscle mitochondrial function in obesity and T2DM and revealed impaired mitochondrial respiration and electron transport chain supercomplex assembly in muscle from patients with T2DM. The first aim was to study the impact of T2DM on weight loss ability in a large population of obese patients participating in a standardized meal replacement and lifestyle modification program. As there is considerable variability in weight loss propensity, it was found that T2DM significantly deters weight loss although the effect is not large. Since skeletal muscle energetics are central in the development and progression of obesity and T2DM, the second and third aims were to study mitochondrial function in this tissue with the idea of uncovering molecular etiologies. The second aim found deficiencies in mitochondrial respiration in individuals with obesity and T2DM compared to individuals with obesity alone. Reductions in mitochondrial respiration were correlated with increasing levels of HbA1C and attributed to paucity in supercomplex formation in the mitochondrial inner membrane (MIM) of the electron transport chain (ETC). The third aim was to delineate differential fuel oxidation mechanisms and circulating protein biomarkers in obese diet-sensitive (ODS) and obese diet-resistant (ODR) participants following a high fat meal (HFM) challenge. Whole-body analyses were conducted in addition to measures in blood, adipose tissue, skeletal muscle and primary cells. Remarkable increases in oxidative capacity were measured post-HFM. In addition, impaired mitochondrial function was found in the ODR group despite lack of differences in mitochondrial content or the assembly of supercomplexes. Differences were also found in circulating acylcarnitines as well as expression of several proteins including Heat shock 70 kDa protein 1A/1B, Tyrosine-protein kinase Fgr, and Peptidyl-prolyl cis-trans isomerase D. Ultimately, a better understanding of mechanisms involved could lead to significant improvements in personalized medical approaches in obesity and T2DM.
Keywords: Obesity; Type 2 Diabetes Mellitus; Skeletal Muscle; Muscle; Mitochondria; Metabolism; Bioenergetics